2010
DOI: 10.1089/jwh.2009.1623
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity and Pregnancy Decision Making: The Role of Fatalism and Subjective Social Standing

Abstract: Objective: Rates of unintended pregnancy in the United States differ by race and ethnicity. We examined whether these differences might be explained by maternal fatalism and subjective social standing. Methods: We used data from 1070 pregnant women of sociodemographically diverse backgrounds enrolled in prenatal care in the San Francisco Bay area. Logistic regression was used to explore the relationship between attitude variables and a measure of pregnancy decision making (''not trying to get pregnant''). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In an exploration of social standing, an increase in social standing among Black women was not directly related with decreased UIP risk, despite decreases in UIPs among White women of increased social standing. 12,16 Thus, factors beyond SES such as incarceration, perceived discrimination, and social stress may contribute to women's risk for UIP. In this study, the sample of women reflects a generally lower income population; therefore, the racial/ethnic differences observed are likely due to factors beyond SES.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an exploration of social standing, an increase in social standing among Black women was not directly related with decreased UIP risk, despite decreases in UIPs among White women of increased social standing. 12,16 Thus, factors beyond SES such as incarceration, perceived discrimination, and social stress may contribute to women's risk for UIP. In this study, the sample of women reflects a generally lower income population; therefore, the racial/ethnic differences observed are likely due to factors beyond SES.…”
Section: Discussionmentioning
confidence: 99%
“…14 These differences may be impacted by varying attitudes and practices regarding sexuality and family planning based on cultural norms shaped by and reinforced within families and communities. [15][16][17] For instance, Rocca et al 18 reported significant differences in the perception of childbearing between racial/ethnic groups, with childbearing being perceived as more favorable among Asian/Pacific Islander (API) women and unfavorable among White women relative to Black women. 18 Also, pregnancy intention and types of contraception used have been reported to vary between racial/ethnic groups and based on level of education and income.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contraceptive use has also been included in pregnancy intention measurement, despite a robust literature indicating that contraceptive decision making includes many considerations beyond pregnancy intentions, such as side effects, access, affordability and relationship dynamics . As Klerman noted, these measures and the scholarship that relies on them reflect an assumption that “becoming pregnant is a very rational activity based on planning and forethought.” 3(p. 161) Such assumptions may undergird the presumed logical relationship between pregnancy intentions and contraceptive use, and lead to research and interventions that neglect the constellation of factors that inform pregnancy preferences and intentions, including structural ones, such as social position, educational and career opportunities, and experiences of income inequality and poverty …”
mentioning
confidence: 99%
“…It is important to evaluate these relationships among a heterogeneous, at-risk sample as context may influence mothers’ experiences of unintended pregnancies and outcomes associated with unintended pregnancies may be more or less salient depending on mothers’ demographic characteristics. Unintended pregnancies are more common among disadvantaged populations, including women who identify as racial or ethnic minorities (Bryant, Nakagawa, Gregorich, & Kuppermann, 2010), and who are young, unmarried, and with little education (Postlethwaite, Armstrong, Hung, & Shaber, 2010). Additionally, due to the prevalence of unintended pregnancy and because not all women with unintended pregnancies demonstrate compromised parenting practices, it is important to examine factors that may help explain within-group differences among women with unintended pregnancies.…”
mentioning
confidence: 99%